Natural boundary of random Dirichlet series - Ding, Xiaoqing; Xiao, Yimin (Ukrains’kyi Matematychnyi Zhurnal, 2006)
For the random Dirichlet series _n = 0^∞ X_n (ω )e^ - sλ _n (s = σ + it C, 0 = λ _0 < λ _n ∞ ) whose coefficients are uniformly nondegenerate independent random variables, we provide some explicit conditions for the line of convergence to be its natural boundary a.s.